Glandular odontogenic cyst: a report of four cases. Issue 2 (19th January 2017) - Ogura, Ichiro; Tsuchimochi, Makoto; Ono, Junya; Kanri, Yoriaki; Okada, Yasuo; Fujii, Kazuyuki; Yamaguchi, Akira; Sekimoto, Tsuneo
Abstract: A glandular odontogenic cyst is a developmental cyst that is a clinically rare and histopathologically unusual type of odontogenic cyst. In this article, we describe four cases of glandular odontogenic cyst. Glandular odontogenic cyst was defined as a well‐defined unilocular lesion on panoramic radiographs and multidetector computed tomography. Furthermore, the connection of the cyst to the periodontal tissue was one of the common features of the four cases. The results of the present study indicate the clinical and imaging features of glandular odontogenic cyst.